Combinatorial screening of the microstructure–property relationships for Fe–B–X stiff, light, strong and ductile steels. (15th December 2016) - Baron, C.; Springer, H.; Raabe, D.
Abstract: We systematically screened the mechanical, physical and microstructural properties of the alloy systems Fe–10 B–5 X (at.%; X = Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W), in order to identify novel metal matrix composite steels as next generation lightweight materials. The alloys were synthesised and processed by bulk liquid metallurgical techniques, and subsequently analysed for their mechanical and physical properties (i.e. Young's modulus, density, tensile strength and ductility) as well their microstructure and constitution. From the wide variety of observed boride phases and microstructures and resultant different properties, Cr and Zr additions were found to be most effective. Cr qualifies well as the high fraction of M2 B borides of spherical morphology allows achieving a similar stiffness/density ratio and mechanical performance as the reference Ti alloyed materials, but at substantially reduced alloy costs. Zr blended composites on the other hand are softer and less ductile, but the alignment of spiky ZrB2 particles during swaging led to a much higher – though most probably anisotropic – specific modulus. Consequences and recommendations for future alloy and processing design are outlined and discussed. Graphical abstract: Highlights: Systematic screening of mechanical, physical and microstructural properties of Fe–10B–5X alloys for lightweight design Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W additions exhibit widely differing microstructures of different boride phases and mixes Cr and Zr were identified as the most promising elements for design of high modulus steels Fe–B–Cr alloys exhibit similar performance as the established Ti alloyed materials, but at greatly reduced alloying costs Zr alloyed materials are softer and less ductile, but achieve extremely high stiffness/density ratio